The Birth of American Advertising - Mendelová, Dáša (Communication Today, 2018)
The study is focused on the development of advertising in the context of social changes in the US. Its main goal is to point out how advertising reacted to some historical events and important social, economic, political or cultural changes in the US. The study is based on the concept of four crucial moments in the advertising history stated by Holm. He speaks about four phases in the general development of advertising: 1. origins, industrialisation and development, 2. professionalization, consolidation and redemption, 3. manipulation, creativity and globalisation, 4. digital advertising, algorithms and ‘dataveillance’. In this study, the attention is paid to the first phase; however, it is applied to the US historical development and cultural environment. Therefore, the first part of the text points out the nature of advertising from the colonization to the American Revolution; the second and much more extensive part of the study focuses on significant events of the 19th century, which crucially influenced and changed the history of the US, i.e. the Industrial Revolution and the Civil War. Those historical events also affected the ways of promotion; advertising mirrored the situation in society remarkably. The study’s conclusion explains the necessity of regulation and the need for the professional approach towards advertising at the turn of the 20th century.